CGIAR GENDER's Research Exchange System - CGIAR GENDER Impact Platform (CGIAR GENDER Impact Platform, 2022)
The CGIAR GENDER Impact Platform offers a research exchange system that can boost learning and research on gender in agriculture and food systems. Participating in the exchange of resources can help you find the best ways to achieve impact on gender equality, social inclusion and opportunities for youth